Equipping First Aid Learners to Respond in Fragile Environments (International Journal of First Aid Education)
Abstract of conference summarizes how in order to respond to fragile environmnets, first aid education should develop learners into "potential responders" able to perform outside of learning environments where they are unlikely to be supervised or fulley equipped.